The Association Between the Concentration of Serum Magnesium and Postmenopausal Osteoporosis - Chang, Jinlei; Yu, Degang; Ji, Jindou; Wang, Ning; Yu, Shengwen; Yu, Bo (Frontiers in Medicine, 2020)
Abstract Background: Osteoporosis is the most common and widespread chronic skeletal metabolic disease in the world, which can lead to catastrophic fractures. Therefore, it is important to look for factors that can be modified or controlled to prevent osteoporosis. Although serum Mg is believed to be associated with osteoporosis in many individuals, there are conflicting reports on the association between serum Mg and osteoporosis. Therefore, this meta-analyses aimed to explore the association between the concentration of serum Mg and osteoporosis as well as that between the concentration of serum Mg and osteopenia. Methods: Articles were searched in PubMed. We also reviewed the reference lists of the relevant publications and reviews as of December 2019. Finally, 11 eligible studies involving 2,776 postmenopausal women were selected. We also performed subgroup analysis, and publication bias was assessed. Results: According to the forest plot analysis, postmenopausal women with osteoporosis had a lower concentration of serum Mg than normal controls (standardized mean difference [SMD]=−0.56, 95% confidence interval [CI]=−1.02 to −0.09); however, this result was not applicable to those with osteopenia (SMD=−0.30, 95% CI=−0.69 to 0.09). The subgroup analysis by geographical location found a similar pattern in European postmenopausal women with osteoporosis (SMD=−0.73, 95% CI=−1.322 to −0.143), but not in Asian postmenopausal women with osteoporosis (SMD=−0.007, 95% CI=−0.381 to 0.394). Conclusion: Postmenopausal women with osteoporosis have a lower concentration of serum Mg. However, the association between the concentration of serum Mg and osteopenia needs further confirmation.